2022
DOI: 10.1063/5.0077486
|View full text |Cite
|
Sign up to set email alerts
|

Even-order harmonic generation from nonlinear Thomson backscatter in a tightly focused Gaussian laser pulse

Abstract: The electron dynamics and the Thomson backscattering spectra for an electron accelerating in a tightly focused Gaussian laser pulse are first investigated in detail. It is found that for a tightly focused Gaussian laser pulse, the ponderomotive force introduced due to the non-uniform intensity distribution of the laser pulse has the tendency to push out the electron from the laser pulse, which leads to the trajectory symmetry-breaking of the electron and then the generation of the even-order harmonics at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Obviously the maximum photon brightness of the high-order harmonics is larger than that of the low order harmonics in Ref. [44].…”
Section: The Optimum Observation Directionmentioning
confidence: 80%
“…Obviously the maximum photon brightness of the high-order harmonics is larger than that of the low order harmonics in Ref. [44].…”
Section: The Optimum Observation Directionmentioning
confidence: 80%
“…6,11 . Hong et al 12 observed that increasing the laser intensity of a tightly focused Gaussian laser can break the symmetry of electron trajectories and enhance the peak. The effect of laser intensity on the emission spectrum was studied by Zhuang et al 13 , who found that the spectral bandwidth of the emitted light becomes wider in a high-intensity laser field.…”
Section: Introductionmentioning
confidence: 99%
“…(14) Hong et al observed that increasing the laser intensity of a tightly focused Gaussian laser can break the symmetry of electron trajectories and enhance the peak. (15) The effect of laser intensity on the emission spectrum was studied by Zhuang et al, who found that the spectral bandwidth of the emitted light becomes larger in a high-intensity laser field. (16) In addition, Yan et al studied the effect of the initial position of the high-energy electron on its spatial radiation properties.…”
Section: Introductionmentioning
confidence: 99%